1998
DOI: 10.1002/(sici)1096-8652(199810)59:2<171::aid-ajh12>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a patient with cardiac lymphoma who presented with a complete atrioventricular block

Abstract: A patient with primary cardiac lymphoma, which is very rare, generally is regarded to have a poor prognosis. We herein report a patient with cardiac lymphoma who was treated successfully by systemic chemotherapy and radiotherapy using a pacemaker to control the complete atrioventricular (A-V) block. A 70-year-old man had a syncope caused by a complete A-V block. An echocardiogram, a computed tomographic scan, and magnetic resonance imaging of his chest showed a cardiac tumor. At this time, a biopsy of the card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…The finding of EBV nucleic acid sequences in the malignant cells by in situ hybridization has not been previously observed in PCL in immunocompetent patients. 13,14 However, B-cell ALCL has been associated with EBV infection in some cases. 15,16 A unique aspect of this case is the intimate association of the malignant lymphoid cells with a mural fibrin thrombus, without cardiac wall invasion.…”
Section: Resultsmentioning
confidence: 99%
“…The finding of EBV nucleic acid sequences in the malignant cells by in situ hybridization has not been previously observed in PCL in immunocompetent patients. 13,14 However, B-cell ALCL has been associated with EBV infection in some cases. 15,16 A unique aspect of this case is the intimate association of the malignant lymphoid cells with a mural fibrin thrombus, without cardiac wall invasion.…”
Section: Resultsmentioning
confidence: 99%
“…Elbardissi et al reported that atrial fibrillation accompanied 16% of malignant cardiac tumors and ventricular tachycardia was present in 7%. Complete atrioventricular block has been described . Another common finding is electrical alternans characterized by beat‐to‐beat alternation of the QRS complex due to swinging heart within a large pericardial effusion.…”
Section: Common Clinical Featuresmentioning
confidence: 99%
“…Complete atrioventricular block has been described. 16,17 Another common finding is electrical alternans characterized by beat-to-beat alternation of the QRS complex due to swinging heart within a large pericardial effusion.…”
Section: Electrocardiographic and Laboratory Analysesmentioning
confidence: 99%
“…In the English literature, about 20 cases presenting with AV block have been described. Among those cases, a pacemaker was inserted in patients with high degree AV block 16-18). To the best of our knowledge, this case is the first to report on PCL with AV block in the Korean literature.…”
Section: Discussionmentioning
confidence: 92%